Prvotna arhitektura : Tokyo apartment = Primary architecture : Tokyo apartment - Beroš, Ana Dana (2010)
Sou Fujimoto: projekt Tokyo Apartment, Itabashiku, Tokio, Japan
Tekst usporedo na hrv. i engl. jeziku
Keywords: Japanska arhitektura 21. st; Sou Fujimoto; Tokyo apartment (Komone, Itabashiku, Tokio, Japan)